Saphenous Vein Graft Pseudoaneurysm Causing External Compression of the Pulmonary Artery. (August 2019) - Duran Crane, Alejandro; Newtown, Emily; Cremer, Paul; Edward Montané, Bryce; Xu, Bo
Abstract : Supplemental Digital Content is available in the text.